The Influence Of Work Environment On Organizational Culture With Employee Comfort As An Intervening Variable In BPJS Branch Pematang Siantar And BPJS Branch Padang Sidempuan - Sejarahta Perangin-Angin; Mesra B (Best Journal of Administration and Management, 2024)
In this study, researchers wanted to see the direct and indirect effects between work environment variables as independent variables and employee comfort as intervening variables and organizational culture as the dependent variable. This type of research uses quantitative, this research was conducted at the BPJS Employment Branch Office BPJS Pematang Siantar Branch and BPJS Padang Sidempuan Branch. The population of this study was 80 employees and the sample used was all the population using the saturated sample technique. The data source used is primary data sources and the data collection is done by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows Employee comfort has a positive and significant effect on organizational culture with an original sample value of 0.241 and P values of 0.001. The work environment has a positive and significant effect on organizational culture with an original sample value of 0.694 and p values of 0.000. The work environment has a positive and significant effect on employee comfort with an original sample value of 0.637 and p values of 0.000. The work environment has a positive and significant effect on organizational culture through employee comfort directly with the original sample result of 0.151 and p values 0.001.